Hookah smoking impairs nasal mucociliary clearance - Mitat Arıcıgil; Hamdi Arbag (Tobacco Induced Diseases, 2018)
Introduction Active tobacco smoking has been causally associated with nasal mucociliary clearance (MCC). Smoking through a hookah as an alternative to tobacco smoking has been shown in some scientific studies to have several toxic effects on human health. However, no study has been conducted on the effects on nasal MCC of the hookah as an alternative way of smoking tobacco. The aim of this study is to research whether or not hookah affects nasal MCC.